2021
DOI: 10.31014/aior.1994.04.03.184
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke in a Young Adult Female Caused by Takayasu’s Arteritis: A Case Report

Abstract: Takayasu's arteritis is one of the causes of ischemic stroke at a young age, but the occurrence is still rarely reported in Indonesia. Here we report the case of a 19-year-old Indonesian female who was admitted to the Wahidin Sudirohusodo Hospital with a sudden onset of right-sided hemiplegia. Other features of Takayasu’s arteritis were observed, including a discrepancy of more than 10 mmHg between the left and right arm systolic blood pressure, claudication of the extremities, and decreased brachial artery pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Lusida et al reported a case of TA in an 18-yearold woman with recurrent fever and chronic malaise accompanied by headache and claudication of the hands and feet and postprandial abdominal discomfort [4]. The most recent case of TA was reported by Akbar et al, in a 19-year-old woman with ischemic stroke, right hemiplegia, extremity claudication, and decreased left brachial artery pulse [5]. We report a case of rare TA in a young male with clinical manifestation predominantly congestive heart failure and claudication of the left hand.…”
Section: Discussionmentioning
confidence: 99%
“…Lusida et al reported a case of TA in an 18-yearold woman with recurrent fever and chronic malaise accompanied by headache and claudication of the hands and feet and postprandial abdominal discomfort [4]. The most recent case of TA was reported by Akbar et al, in a 19-year-old woman with ischemic stroke, right hemiplegia, extremity claudication, and decreased left brachial artery pulse [5]. We report a case of rare TA in a young male with clinical manifestation predominantly congestive heart failure and claudication of the left hand.…”
Section: Discussionmentioning
confidence: 99%